MYSTERY OF ISOLATED GREATER TROCHANTER FRACTURES: IS THERE MORE THAN MEETS THE EYE? - T, Shival; Harris, Mohammed; Kunalan, Sasidaran; Mohamad, Fazir (International Journal of Allied Health Sciences, 2021)
Isolated greater trochanteric fractures are rare and often treated conservatively. With the newer imaging modalities, there is evidence that these fractures are often accompanied with extensions to the meta-diaphyseal region not seen on plain radiographs. An elderly lady presented with a history of fall. She complained of left hip pain and inability to weight bear. Clinically, there was point tenderness overlying Greater Trochanter and limited range of motion of left hip. Plain radiographs illustrated a Left avulsion greater trochanteric femur fracture. Subsequently, CT scan of the hip showed fracture line extending from the Greater Trochanter till lesser trochanter. The patient was treated with dynamic hip screw and tension band wiring of the greater trochanter. Post operatively, patient was fully weight bearing on day1. At 2months post-op patient was ambulating with normal gait and good hip function. Radiographically documented isolated greater trochanteric fractures have been thought to be uncommon. Because of their purported rarity, greater trochanteric fractures are hardly included conventional hip fracture classifications However, according Yunus et al, 31 out of 40 patients that seemingly had isolated greater trochanter fractures had incomplete inter-trochanteric extensions on MRI. Increasing incidence of occult fractures diagnosed on further imaging brings about our proposal that these fractures should be treated surgically like above. The procedure is short, cheap, safe and allows immediate weight bearing. The potential consequences of missing these occult fractures include fracture displacement, late weight bearing, longer immobilization. We recommend that patients with an isolated greater trochanter fracture on the plain radiographs should undergo CT/MRI examination and those with intertrochanteric extensions undergo surgery. The surgical methods of addressing isolated greater trochanter fractures merit further investigation